2019
DOI: 10.29333/ejmste/106258
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis of the Representations of Functions in the University Entrance Exam in Spain and Iran

Abstract: The University Entrance Exam (UEE) has an important impact on how math instructors teach mathematics to prepare students for this exam as well as how their students learn mathematics. Since the UEE is like a bridge between high school and university, its importance becomes twofold. However, research regarding this issue is very limited in mathematics education. The purpose of this research is to conduct an exploratory analysis of mathematics questions from the UEE in Spain and Iran from the point of view of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Lately, teachers have been emphasizing the mastery of problem-solving techniques akin to those found on the Konkoor (Farrokhi-Khajeh-Pasha et al, 2012). Acquiring these methods involves memorizing numerous formulas that have no utility outside of this specific exam context (Borji & Sánchez, 2019). In contrast, in a Canadian classroom, students are not required to memorize formulas, and teachers often provide them with a formula sheet during tests.…”
Section: Methodsmentioning
confidence: 99%
“…Lately, teachers have been emphasizing the mastery of problem-solving techniques akin to those found on the Konkoor (Farrokhi-Khajeh-Pasha et al, 2012). Acquiring these methods involves memorizing numerous formulas that have no utility outside of this specific exam context (Borji & Sánchez, 2019). In contrast, in a Canadian classroom, students are not required to memorize formulas, and teachers often provide them with a formula sheet during tests.…”
Section: Methodsmentioning
confidence: 99%
“…(Behr et al, 1983). Various authors study the relationship between modes of representation of tasks and their understanding, or between the use of the concept image and its definition (Borji et al, 2018;Borji & Sánchez, 2019;Dahl, 2017;Pinto-Rojas & Parraguez, 2017). identified three levels of understanding of the derivative scheme (intra-inter-trans), which are based, among other aspects, on different modes of representation.…”
Section: Introductionmentioning
confidence: 99%
“…identified three levels of understanding of the derivative scheme (intra-inter-trans), which are based, among other aspects, on different modes of representation. Moreover, Borji and Sánchez (2019) concluded that the predominant mode of representation in secondary education is algebraic. For this reason, first-year undergraduate students may have difficulties in solving problems in other modes of representation or finding relations between them.…”
Section: Introductionmentioning
confidence: 99%